PENGARUH E-SERVICE QUALITY DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN E-COMMERCE PADA SISWA/SISWI DI SEKOLAH MENENGAH KEJURUAN - Laurensius Arliman Simbolon (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
This research provides several important implications, especially for owners / managers of e-commerce websites in order to increase their understanding in dealing with online consumer tastes. One of them is by improving the quality of the website that is presented, so that user confidence increases with the quality of the e-commerce website that is presented. The implications of this study indicate that e-service quality or which is more directed to the quality of services on e-commerce websites is very important for website users, especially students. With the quality of services on the website that is presented, it will certainly be able to increase user confidence. Especially with the type of goods that are often bought by students and students who are known to have quality products such as clothes, airplane tickets, books, and other things. To create high loyalty, online business people who manage e-commerce websites should be able to improve the quality of services on their websites, so that later trust will be higher in using e-commerce websites.